Membidik Arus Globalisasi dari Perspektif Idiologi Indonesia - I Made Priana (SANCTUM DOMINE: JURNAL TEOLOGI, 2016)
This paper tries to explain globalisation in light of Indonesian ideology as contained in the Pancasila. Having grasped the current of globalisastion informed by the values of Pancasila, we must drive the current of globalisation in keeping with the spirit of Indonenesia. In other words, the identityand values of Indonesia must inform anddrive globalisation. The ideology of Indonesia has to become the soul of globalisation. Globalisation without the spirit of Indonesia will not help us to reach the goals of our Nation, the wellbeing of Indonesian. On the contrary, globalisation informed by the spirit of Indonesia is will help us to embody the aim of our Nation, which is the wellbeing of all Indonesians.